Citrullination and Carbamylation in the Pathophysiology of Rheumatoid Arthritis - Pruijn, Ger J. M. (Frontiers in Immunology, 2015)
The discovery that citrullination was crucial for the recognition of antigens by the most disease-specific class of autoantibodies in rheumatoid arthritis had a huge impact on studies aimed at understanding autoimmunity in this disease. In addition to the detailed characterization of anti-citrullinated protein antibodies, various studies have addressed the identity of citrullinated antigens. These investigations were facilitated by new methods to characterize these proteins, the analysis of protein citrullination by peptidylarginine deiminases, the generation of a catalogue of citrullinated proteins present in the inflamed joints of patients and the finding that the formation of extracellular traps is dependent on the activity of peptidylarginine deiminase activity. Recently, it was found that in addition to citrullination also carbamylation, which results in chemically highly related modified proteins, yields antigens that are targeted by rheumatoid arthritis patient sera. Here, all of these aspects will be discussed, culminating in current ideas about the involvement of citrullination and carbamylation in pathophysiological processes in autoimmunity, especially rheumatoid arthritis.